Pengembangan Sistem Manajemen Wisma La Tibel Palangka Raya Berbasis Web dan SMS Gateway - Timothy Nataniel Magat; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wisma La Tibel is a boarding house located in Palangka Raya City, Central Borneo. The owner has owned three boarding houses until now: Wisma La Tibel 1, Wisma La Tibel 2, and Wisma La Tibel 3. Wisma La Tibel 1 and Wisma La Tibel 2 have 16 rooms and Wisma La Tibel 3 has 8 rooms. All boarding houses are located in the same city but in different addresses. The main job of the owner is to manage every boarding house. Currently, the owner has some problems in doing so such as inaccuracy in managing data of income and bills of all boarding houses. A management system is developed in order to solve those problems and to be able to manage every boarding house. This management system is web based and has SMS gateway feature to sending monthly bills to tenants. This system will easily help the owner to integrate all boarding houses because the owner can manage three boarding houses with only one system. This boarding house management system has been tested using 2 testing techniques, white box (unit testing and integration testing) and black box (validation testing). The results from all testing that have been done are 100% valid.